Analisa Rasio Keuangan Terhadap Kinerja Perusahaan Pada Industri Perbankan : PT Bank BRI, PT Bank BNI, PT Bank Mandiri, Dan PT Bank BCA - Yuli Meliana; Joanne Intania Rut Simunapendi; Ajeng Rossantika Sari; Fitri Sulistiyana; Cholis Hidayati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The rapid development of the banking world and the high level of complexity of the banking business can affect the financial performance of a bank. Bank financial statements can be used as a measure of a bank's performance by analyzing financial statements through ratio analysis. to assess the financial performance and market share of banks using ratios including liquidity ratios, activity ratios, profitability ratios, leverage ratios and special ratios. The method used in this research is descriptive analysis through a quantitative approach to be the research method used. Quantitative data type, with data collection techniques through internal in the form of financial reports from PT Bank BNI, PT Bank BRI, PT Bank BCA, and PT Bank Mandiri obtained from the Indonesia Stock Exchange (IDX) website. This study shows that there are significant differences to assess the financial performance and market share of banks using ratios including liquidity ratios, activity ratios, profitability ratios, leverage ratios and special ratios..